Transactions Transfer Pricing Policies and Performance of Corporate Organizations’ in Nigeria - Osho, Augustine E.; Shaka, Abdulrahman (The Journal of Accounting and Management, 2023)
The study examined the effect of transaction transfer pricing policies on performance of corporate organization. Specifically, the study investigates the effect of target price, interest rate, inflation rate and exchange rate on profit after tax of listed food and beverage companies in Nigeria. The study sampled 5 companies out of 21 companies, the study employed secondary data and the data were collated from the financial reports of the sampled companies over 10 years (2012 - 2021). The study utilized panel regression analysis techniques. The fixed effect result revealed that transfer price and interest rate maintained positive but insignificant relationship with profit after tax with coefficient of 0.222465 (p = 0.3297 > 0.05) and 0.151676 (p = 0.0074 > 0.05), while, inflation rate and exchange rate were found to be negatively and insignificantly related to with coefficient -0.598881 (p = 0.5331 > 0.05) and -0.051286 (p = 0.5919 > 0.05) The study concluded that transactions transfer pricing policies has both positive and negative influence on performance of corporate organization. Especially, when measured in terms of profit after tax. Based on this finding, it was recommended that food and beverage companies should develop a mechanism to hedge against exchange rate and inflation rate caused by anticipated adjustment on exchange and inflation rates.